Sense and Mind method: an innovative methodological approach to embodied rehabilitation - Annalisa Risoli; Alessandro Antonietti; Laura Colautti; Sara Magenes; Giulia Purpura; Leonardo Fogassi (Cognitive Processing, 2026)
As neurorehabilitation research expands, it is crucial to ensure that scientific findings are integrated into neurorehabilitation clinical practice. Building on evidence about embodied cognition, this paper proposes an innovative method called Sense and Mind (SaM), designed for individuals with neurodevelopmental and acquired neurocognitive and neuromotor impairments. It aims to rehabilitate spatial cognition and executive functions from the patient’s bodily experience. A description of the theoretical bases of the SaM method is provided. Theory construct involves neuroscientific evidence relative to embodied cognition, movement and action, spatial representation, mental imagery, and executive functions. Furthermore, a description of the methodological structure is outlined, allowing for interventions with the patient at different levels of complexity and with various goals through a restitutive approach, ranging from programming voluntary movement to constructing and using mental images. Through different goal-directed activities based on multimodal sensory experiences, the SaM method focuses on recovering executive functions, which are crucial for daily life. The SaM method, through an individualised approach based on each patient’s psychomotor profile, can be helpful for neuromotor and neuropsychological rehabilitation of several types of disabilities. Further studies are necessary to investigate its efficacy on larger samples of patients.

Divergent thinking and the core executive functions: a state-of-the-art review - Massimiliano Palmiero; Giulia Fusi; Maura Crepaldi; Virginia Maria Borsa; Maria Luisa Rusconi (Cognitive Processing, 2022)

Investigating how internet gaming disorder and bodily dissociation experiences vary by game genres - Silvia Casale; Giulia Fioravanti; Alessia Musicò (Cognitive Processing, 2022)

Long-term meditation: the relationship between cognitive processes, thinking styles and mindfulness - Rosa Angela Fabio; Giulia Emma Towey (Cognitive Processing, 2018)

Single-case study in rehabilitation with SaM method (Sense and Mind): a proposal and analysis - Annalisa Risoli; Adriana Bortolotti; Manuela Capettini; Giulia Giacobbi; Marina Ramella (Cognitive Processing, 2015)

The role of the posterior parietal cortex in stereopsis and hand-eye coordination during motor task behaviours - Giulia Paggetti; Daniel Richard Leff; Felipe Orihuela-Espina; George Mylonas; Ara Darzi; Guang-Zhong Yang; Gloria Menegaz (Cognitive Processing, 2015)

Using brain–computer interfaces to overcome the extinction of goal-directed thinking in minimally conscious state patients - Giulia Liberati; Niels Birbaumer (Cognitive Processing, 2012)

Cognitive reserve and its implications for rehabilitation and Alzheimer’s disease - Giulia Liberati; Antonino Raffone; Marta Olivetti Belardinelli (Cognitive Processing, 2012)

Reorientation ability of adults and healthy children submitted to whole body horizontal rotations - Giulia Zanelli; Maurizio Petrarca; Paolo Cappa; Enrico Castelli; Alain Berthoz (Cognitive Processing, 2009)

Music-to-language transfer effect: may melodic ability improve learning of tonal languages by native nontonal speakers? - Franco Delogu; Giulia Lampis; Marta Olivetti Belardinelli (Cognitive Processing, 2006)